Penyusunan Skala Penyesuaian Diri Perempuan Pekerja (SPDPP) - Eustalia Wigunawati; Formas Juitan Lase; Audra Jovani; Evi Evi Deliviana (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
Women who work and have multiple roles allow them to face various challenges, obstacles and experience certain psychological impacts. To face these challenges, it is important for women who work and have multiple roles to adapt. This study aims to develop a valid and reliable adjustment tool for working women, which can be used as material for selecting or evaluating female employees in a company or can be used for working women who have multiple roles in general. This study used a quantitative approach. This research is designing a psychological scale. Respondents in this study were 389 women who worked and had multiple roles. This research produced a measurement tool called the Working Women Self-Adjustment Scale (SPDPP). SPDPP consists of 15 items that have good item discrimination and represent five aspects of adjustment evenly, where each aspect consists of 3 items. This measurement tool has good validity based on construct validity, where the value of the item-rest correlation ranges from 0.337 to 0.513. This measuring instrument also has high Cronbach's Alpha reliability with a Cronbach's Alpha value of 0.798.